Nonsense mediated RNA decay and evolutionary capacitance - Raxwal, Vivek Kumar; Riha, Karel (Biochimica et biophysica acta, 2016)
Nonsense mediated RNA decay (NMD) is well-known as an RNA quality control mechanism that sequesters a substantial portion of RNA from expression by targeting it for degradation. However, a number of recent studies across a range of organisms indicate a broader role for NMD in gene regulation and transcriptome homeostasis. Here we propose a novel role for NMD as a buffering system with the capability of accumulating and subsequently releasing a wide spectrum of cryptic genetic variation in response to environmental stimuli, and hence facilitating adaptive evolution. We discuss this role for NMD in the context of evolution of plant pathogen defense, whereby NMD may promote rapid diversification of intracellular immune receptors by mitigating the potentially harmful impact of their newly formed variants on plant fitness.
Keywords: nesmyslný kodon; Gene Expression Regulation; Plant defense; Cryptic genetic variation; transkriptom; Codon, Nonsense; RNA, Messenger; Transcriptome; Evolvability; Nonsense Mediated mRNA Decay; NB-LRR immune receptors; RNA; messenger RNA; nonsense mediated mRNA decay; regulace genové exprese; Gene duplication